Sodium–Glucose Co-Transporter 2 Inhibition With Empagliflozin Improves Cardiac Function After Cardiac Arrest in Rats by Enhancing Mitochondrial Energy Metabolism - Tan, Yunke; Yu, Kai; Liang, Lian; Liu, Yuanshan; Song, Fengqing; Ge, Qiulin; Fang, Xiangshao; Yu, Tao; Huang, Zitong; Jiang, Longyuan; Wang, Peng (Frontiers in Pharmacology, 2021)
Empagliflozin is a newly developed antidiabetic drug to reduce hyperglycaemia by highly selective inhibition of sodium–glucose co-transporter 2. Hyperglycaemia is commonly seen in patients after cardiac arrest (CA) and is associated with worse outcomes. In this study, we examined the effects of empagliflozin on cardiac function in rats with myocardial dysfunction after CA. Non-diabetic male Sprague–Dawley rats underwent ventricular fibrillation to induce CA, or sham surgery. Rats received 10 mg/kg of empagliflozin or vehicle at 10 min after return of spontaneous circulation by intraperitoneal injection. Cardiac function was assessed by echocardiography, histological analysis, molecular markers of myocardial injury, oxidative stress, mitochondrial ultrastructural integrity and metabolism. We found that empagliflozin did not influence heart rate and blood pressure, but left ventricular function and survival time were significantly higher in the empagliflozin treated group compared to the group treated with vehicle. Empagliflozin also reduced myocardial fibrosis, serum cardiac troponin I levels and myocardial oxidative stress after CA. Moreover, empagliflozin maintained the structural integrity of myocardial mitochondria and increased mitochondrial activity after CA. In addition, empagliflozin increased circulating and myocardial ketone levels as well as heart β-hydroxy butyrate dehydrogenase 1 protein expression. Together, these metabolic changes were associated with an increase in cardiac energy metabolism. Therefore, empagliflozin favorably affected cardiac function in non-diabetic rats with acute myocardial dysfunction after CA, associated with reducing glucose levels and increasing ketone body oxidized metabolism. Our data suggest that empagliflozin might benefit patients with myocardial dysfunction after CA.